Analisis Return On Asset (ROA), Return On Equity (ROE), Dan Net Profit Margin (NPM), Pada Pertumbuhan Laba Perusahaan Properti Dan Real Estate - Az Zahra, Nurul Rizki; Azizah, Nur (IJAcc, 2025)
This study aims to analyze the profit growth of property and real estate companies that occurred after the covid-19 period which resulted in 12 companies experiencing delays in financial reports due to potential losses or decreases in profits. The data used in this study are secondary data totaling 96 samples with purposive sampling method. The tests used to analyze the relationship between the independent variable and the dependent variable are descriptive statistical analysis, classical assumption test, multiple linear regression, coefficient of determination, partial and simultaneous. The findings of this study identify that partially Return On Asset, Return On Equity, Net Profit Margin have an influence on profit growth. Simultaneously, the three variables also have an influence on profit growth. This means that property and real estate companies are able to maximize their net profit, equity, assets, and sales so as to increase the company's profit growth.